Do Owner Characteristic, Technology Usage, and Product Competence Affect Small Business Performance? - Cahyati, Ni Kadek Dwi (APPS Publications, 2022)
The purpose of the research is to evaluate the factors of owner characteristics, technology usage, and product competence toward small business performance. The research model was tested using a survey of 64 small business shoppers in Jakarta. The research findings indicate that owner characteristics, technology usage, and product competence affect small business performance. The results point to the importance of owner characteristics, technology usage, and product competence factors in understanding small business performance.